Theorising the doctrine of joint criminal enterprise in international criminal law - Jain, N (2010)
This thesis develops a theoretical account of the basis and justification for the doctrine of Joint Criminal Enterptise in international criminal law by examining principles governing the ascription of criminal responsibility in English and German criminal law. The first part consists of a comprehensive review of the development of the JCE doctrine, including its historical antecedents, its initial formulation by the ICTY, its subsequent explication by tribunals and academics, and recent alternatives doctrines proposed by the ICC and by commentators. It identifies the main loopholes and contradictions in the construction of these theories, and presents factual scenarios for which these theories, particularly JCE, either have no answers, or problematic ones. The second part examines whether any of the variants of JCE can be justified as principal responsibility. It first identifies elements that distinguish international crimes from their domestic counterparts, and which are pertinent in developing an account of criminal responsibility for international crimes. It also examines the concept of perpetration responsibility in English and German criminal law and theory. It then combines the insights gleaned from these analyses to conclude that only JCE I can be appropriately considered as perpetrator responsibility and proposes a modified version of the doctrine of Organisationsherrschaft in German criminal law as a more accurate characterisation of the role and function of high level participants in mass atrocity. The final part focuses on the concept of accomplice responsibility in German and English criminal law and doctrine to address whether JCE II and JCE III can be justified as modes of secondary criminal responsibility. It concludes that JCE II and JCE III can be retained as distinct modes of accomplice liability using expressive and risk justifications, provided their operation is limited in ways that correspond to principles of secondary responsibility in domestic jurisdictions.